2016
DOI: 10.1016/j.anbehav.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

School level structural and dynamic adjustments to risk promote information transfer and collective evasion in herring

Abstract: 1 transfer and collective evasion in herring 2 3Many large-scale animal groups have the ability to react in a rapid and coordinated manner to 4 environmental perturbations or predators. Information transfer among organisms during such 5 events is thought to confer important antipredatory advantages. However, it remains unknown 6 whether individuals in large aggregations can change the structural properties of their 7 collective in response to higher predation risk, and if so whether such adjustments promote 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…The variability of within group inter‐individual spacing was also affected by the presence of a dolphin within the school (Fig. ) with a marked decrease in variability when dolphins were present, even when controlling for taxa, similar to the increase in organization observed in individual schools in experiments exposing the group to a predator, a process shown to improve collective responsiveness to risk (Rieucau et al ). Note, however, that unlike observations on fish schools which respond more intensely at high densities (Rieucau et al ), we observed very similar responses by squid over a range of packing densities (here measured as inter‐individual distance), a measurement that was positively correlated with the target strength (e.g., length) of individual squid that made up each group in the absence of observed predation pressure.…”
Section: Resultsmentioning
confidence: 69%
“…The variability of within group inter‐individual spacing was also affected by the presence of a dolphin within the school (Fig. ) with a marked decrease in variability when dolphins were present, even when controlling for taxa, similar to the increase in organization observed in individual schools in experiments exposing the group to a predator, a process shown to improve collective responsiveness to risk (Rieucau et al ). Note, however, that unlike observations on fish schools which respond more intensely at high densities (Rieucau et al ), we observed very similar responses by squid over a range of packing densities (here measured as inter‐individual distance), a measurement that was positively correlated with the target strength (e.g., length) of individual squid that made up each group in the absence of observed predation pressure.…”
Section: Resultsmentioning
confidence: 69%
“…Further efforts should be directed at implementing automated video post‐processing to track and quantify swimming dynamics. Recent advances in automated tracking techniques such as the use of particle image velocimetry (PIV) allow researchers to measure swimming dynamics and collective reactions of pelagic fish with great precision, even in very dense shoals (Rieucau et al , a,b). To overcome the important challenge of controlling for the drone movement, our tracking algorithm could be implemented with optic‐flow based techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Automated tracking techniques, such as the use of particle image velocimetry, have been successfully employed by researchers to measure collective reactions of pelagic fish (Rieucau et al. , ). A current challenge for the further development of UAS video analysis resides in the capability to estimate and subtract the UAS's movement.…”
Section: Equipment and Applicationmentioning
confidence: 99%
“…employed by researchers to measure collective reactions of pelagic fish (Rieucau et al 2016a(Rieucau et al , 2016b. A current challenge for the further development of UAS video analysis resides in the capability to estimate and subtract the UAS's movement.…”
mentioning
confidence: 99%